Prevention of central venous line associated bloodstream infections- A literature review - Kashif Khan; Tariq Ali (LIAQUAT MEDICAL RESEARCH JOURNAL, 2024)
Hospital-acquired infections, particularly Central Venous Line-Associated Bloodstream Infections (CLABSIs), are a noteworthy concern in intensive care units (ICUs). CLABSIs not only extend hospital stays but also increase healthcare costs and pose serious threats to patients' well-being. This narrative literature review explores the evidence-based strategies for the prevention of CLABSIs in critical care settings. It emphasizes the importance of proper infection control measures, such as hand hygiene, maximal barrier precautions, and chlorhexidine skin preparation, to reduce the risk of infection. The choice of catheter insertion site, duration of catheter use, and nurse-patient ratios are also discussed as crucial factors in CLABSI prevention. Additionally, post-insertion care, including daily bathing with chlorhexidine, catheter patency maintenance, and dressing changes, is highlighted. The review underscores the need for healthcare workers to adhere to best practices and guidelines to minimize CLABSI rates, ultimately enhancing patient safety and reducing healthcare burdens. The findings emphasize the significance of informed practices in preventing CLABSIs and the potential for improved patient outcomes with their implementation.